Distinct inflammatory signatures of upper and lower body adipose tissue and adipocytes in women with normal weight or obesity - Lempesis, Ioannis G.; Hoebers, Nicole; Essers, Yvonne; Jocken, Johan W. E.; Dineen, Rosemary; Blaak, Ellen E.; Manolopoulos, Konstantinos N.; Goossens, Gijs H. (Frontiers in Endocrinology, 2023)
Introduction: Upper and lower body fat accumulation pose opposing obesity-related cardiometabolic disease risk. Depot-differences in subcutaneous adipose tissue (SAT) function may “underlie these associations. We aimed to investigate the inflammatory signatures of abdominal (ABD) and femoral (FEM) SAT in postmenopausal women with normal weight or obesity. Methods: We included 23 postmenopausal women with normal weight (n=13) or obesity (n=10). In vivo secretion of adipokines from ABD and FEM SAT was measured using the arterio-venous balance technique. Adipokine gene expression and adipocyte morphology were examined in ABD and FEM SAT. Furthermore, adipokine expression and secretion were investigated in vitro using differentiated human primary ABD and FEM subcutaneous adipocytes derived from the study participants. Results: Plasma leptin and PAI-1 concentrations were higher, and ABD and FEM adipocytes were larger in women with obesity than normal weight. No differences in adipocyte size and blood flow were apparent between ABD and FEM SAT. We found significant release of leptin and MCP-1 from ABD and FEM SAT, with higher fractional release of MCP-1 from ABD than FEM SAT. Gene expression of leptin, PAI-1 and TNF-α was lower in ABD than FEM SAT, and higher in women with obesity than normal weight. In ABD adipocytes, IL-6, PAI-1, and leptin gene expression was higher, while adiponectin and DPP-4 gene expression were lower than in FEM adipocytes. Finally, ABD adipocytes secreted less MCP-1 compared to FEM adipocytes. Discussion: These findings demonstrate that upper and lower body SAT and adipocytes are characterized by distinct inflammatory signatures in postmenopausal women, which seem independent of adipocyte size.